2010
DOI: 10.1038/cr.2010.111
|View full text |Cite|
|
Sign up to set email alerts
|

Baicalin inhibits PDGF-BB-stimulated vascular smooth muscle cell proliferation through suppressing PDGFRβ-ERK signaling and increase in p27 accumulation and prevents injury-induced neointimal hyperplasia

Abstract: The increased proliferation and migration of vascular smooth muscle cells (VSMCs) are key events in the development of atherosclerotic lesions. Baicalin, an herb-derived flavonoid compound, has been previously shown to induce apoptosis and growth inhibition in cancer cells through multiple pathways. However, the potential role of baicalin in regulation of VSMC proliferation and prevention of cardiovascular diseases remains unexplored. In this study, we show that pretreatment with baicalin has a dose-dependent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(71 citation statements)
references
References 33 publications
2
66
0
1
Order By: Relevance
“…Baicalin downregulates proto-oncogenes c-jun and c-fos as well as down-regulation of miR-294 expression in mESCs while overexpression of miR-294 in mESCs reverses the alterations in the mESC proliferation and the expression of c-jun and c-fos induced by baicalin. Our results are in good agreement with the observations in cancer cells and vascular smooth muscle cells (VSMCs) [74,75] . Since recent reports have implicated miRNAs in the regulation of proliferation, differentiation and apoptosis in cancer cells and ESCs, it seems possible that miRNAs might also contribute to the cellular mechanisms of decreased proliferation and differentiation and increased apoptosis induced by baicalin in cancer cells.…”
Section: Baicalinsupporting
confidence: 82%
“…Baicalin downregulates proto-oncogenes c-jun and c-fos as well as down-regulation of miR-294 expression in mESCs while overexpression of miR-294 in mESCs reverses the alterations in the mESC proliferation and the expression of c-jun and c-fos induced by baicalin. Our results are in good agreement with the observations in cancer cells and vascular smooth muscle cells (VSMCs) [74,75] . Since recent reports have implicated miRNAs in the regulation of proliferation, differentiation and apoptosis in cancer cells and ESCs, it seems possible that miRNAs might also contribute to the cellular mechanisms of decreased proliferation and differentiation and increased apoptosis induced by baicalin in cancer cells.…”
Section: Baicalinsupporting
confidence: 82%
“…Therefore, tumor growth and metastasis are dependent on angiogenesis and lymphangiogenesis (14)(15)(16). Recently, several studies found that baicalein inhibited proliferation of smooth muscle cells and inhibited LPS-induced angiogenesis in vascular endothelial cells (6,17). Baicalein was also found to inhibit endothelial cell proliferation by inhibiting VEGFR-2 phosphorylation and to decrease the activity of MMP-2 in endothelial cells (18,19).…”
Section: Introductionmentioning
confidence: 99%
“…Baicalein was found to inhibit the proliferation of vascular smooth muscle cells (VSMCs) in cardiovascular disease (24). notably, baicalein inhibited the expression of VEGF and FGFR-2, leading to anticancer effects in lung cancer (20).…”
Section: Cell Proliferationmentioning
confidence: 99%
“…Kip1 is regulated by multiple signaling pathways, including the Ras/MAPK/ERK1/2 [33][34][35] and PI3K/Akt/mTOR pathways. 36,37 These observations prompted us to examine the impact of rapamycin on The levels of p-p70S6K and p70S6K were analyzed by Western blotting.…”
Section: Discussionmentioning
confidence: 99%